Implementation of Drill Method in Learning to BTQ (Baca Tulis al-Qur’an) in TPQ (Taman Pendidikan al-Qur’an) - Agus Miftakus Surur; Laelatul Elmi; Dwi Kansa Putra; Maulina Putri Wulandari; Rizqi Rochmah; Amalila Susanti (IJUS | International Journal of Umranic Studies, 2023)
The purpose of this research is to describe the ways to teach reading the Qur'an and understand basics, and knowledge of recitasion of the Qur'an from an early age, as well as how to write hijaiyah letters in TPQ (Taman Pendidikan al-Qur’an (qur’an learning center)) through assistance using the drill method. This is based on the problems found that many students can recite the Qur'an, but still cannot understand the tajwid and how to write hijaiyah letters correctly. For this reason, researchers conducted further research using the PAR (Participatory Action Research) method. The PAR method is a research method that is carried out in a participatory manner between people in a community that encourages transformative actions to make changes to have better living conditions. The result of this study showed that the implementation of BTQ (Baca Tulis al-Qur’an (writing and reading the qur’an)) assistance with the drill method was found to have better than before. Students can understand the recitation lessons that are drilled and can apply them when reading the Qur’an.